2006
DOI: 10.1002/bit.21022
|View full text |Cite
|
Sign up to set email alerts
|

Development of an electrochemical antifouling system for seawater cooling pipelines of power plants using titanium

Abstract: Biofouling is the undesirable adhesion and development of microorganisms and macroorganisms in a water environment. An electrochemical antifouling system based on management of primary adhesion of microorganisms was developed employing titanium electrode for antifouling of seawater cooling pipes and marine infrastructures. The system consists of an electrochemical reaction-monitoring unit, a power control unit, and a potential/current remote monitoring and a control unit. Titanium plates and iron plates were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 26 publications
1
26
1
Order By: Relevance
“…Indeed, oxygen reduction and hydrogen peroxide production have been reported in anodically produced TiO 2 (Clechet et al 1979;Mentus 2004). Moreover, Wake et al (2006) presented a similar conclusion regarding the involvement of reactive oxygen species on electro chemical AF processes using titanium electrodes. Thus, further investigation of these systems is necessary in order to evaluate the importance of reactive oxygen species formation on the inhibition of barnacle settlement.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Indeed, oxygen reduction and hydrogen peroxide production have been reported in anodically produced TiO 2 (Clechet et al 1979;Mentus 2004). Moreover, Wake et al (2006) presented a similar conclusion regarding the involvement of reactive oxygen species on electro chemical AF processes using titanium electrodes. Thus, further investigation of these systems is necessary in order to evaluate the importance of reactive oxygen species formation on the inhibition of barnacle settlement.…”
Section: Discussionsupporting
confidence: 60%
“…This energy value is higher than the one reported by Wake et al (2006) for an AF study using galvanometrically activated titanium plates in a field system (0.3-0.6 W h 71 m 72 or, equivalently, 50-100 mA m 72 of current with an average voltage of 6 V vs. Ag/AgCl reference electrode). Voltage drops occurring at the counter electrode were not reported in that study, thus a direct comparison with the present results cannot be established.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…However, the detached bacteria could again accumulate on the surface, which caused prolongation of bacterial adhesion. On the other hand, direct electron transfer between bacteria and the anode surface has been applied to prevent microbial adhesion, biofilm growth, and marine biofouling [170,172,173]. When an anodic current or potential is applied, inactivated bacteria tend to remain on the surface.…”
Section: Electro-assisted Methodsmentioning
confidence: 99%
“…In saline waters electrochemical polarization can generate biocidally active chlorine species (Cl 2 , HCl, OCl ¡ , and ClO 2 ) that are most likely responsible for the reported antimicrobial activity and antifouling in marine applications [16,28]. We found that electrochemical polarization was eVective also in brackish Baltic Sea water (3 g NaCl l ¡1 ) used as cooling water in heat exchangers of a power plant [13].…”
Section: Introductionmentioning
confidence: 98%